STRATEGI DIVISI OPERASIONAL DALAM MENINGKATKAN KUALITAS PELAYANAN RAMAYANA BALLET PRAMBANAN YOGYAKARTA - , HANTIO ANUNG WIDIGDO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to determine how to improve the quality of operational services division Ramayana Ballet Prambanan in Yogyakarta. Operational Division is in charge of the division that caters to tourists. In the Operations Division, perform various tasks including receiving visitors and travelers requesting admission, invited tourists taking synopsis, directing tourists entered the stage, take tourists to the seat. Service is an activity or sequence of activities that occur in the direct interaction between a person and another person or physical machines, and provide customer satisfaction.